PEMANFAATAN DROSOPHILA MELANOGASTER SEBAGAI ORGANISME MODEL UNTUK MEMPELAJARI PENGARUH FAKTOR LINGKUNGAN TERHADAP EKSPRESI SIFAT MAKHLUK HIDUP PADA PERKULIAHAN GENETIKA - Shefa Dwijayanti Ramadani; Aloysius DUran Corebima; Siti Zubaidah (Pascasarjana Universitas Negeri Malang, 2016)
The interaction between genetic and environmental factors in determining the characters of living organism is one of the main concepts in biology nowadays, and it becomes one of the main topic that students learn in genetics lecture. However, the observation result showed that regulation of gene expression in eukaryotes was considered to be a quite difficult topic for the students. The utilization of Drosophila melanogaster through practical activities can be used as an instructional media to help students understand the effect of environmental factors on the characters of living organism. This research aims to prove that through the crossbreeding of D. melanogaster for several generations, the effect of environmental factors on the characters of living organism can be observed. In this research, three strains of D. melanogaster were used to reveal the effect of dark environment on fecundity, which is one of the determinant factors of fitness in insects. The results showed that D. melanogaster treated in dark condition had lower fecundity than that in the control condition. The results of the comparison among the strains also showed that the strains of wild-type had higher fecundity than the white eyed color and ebony strains. The interaction between light conditions and generation and the interaction between light, strains, and generation also had an effect on the fecundity.